Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan dan Beban Pajak Tangguhan Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia) - Puspita, Indah Lia; Lestari, Lesti (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2020)
The company was established with the aim of making as much profit as possible, the owner usuallygave up the company's resources to be managed by management. The research objective is to test,prove and know the effect of profitability, leverage, firm size, deferred tax burden on earningsmanagement. this research was conducted at banking companies listed on the Indonesia StockExchange. The number of samples in this study were 20 companies that had met the criteria in thestudy. The results in this study show that, profitability, firm size, deferred tax expense have aninfluence on earnings management while leverage, and tax planning have no influence.Keywords: Profitability, Leverage, Company Size, Deferred Tax Expenses1